1999
DOI: 10.1037/0022-0663.91.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in writing self-beliefs of elementary school students.

Abstract: The authors investigated the nature of gender differences in the writing self-beliefs of elementary school students in Grades 3, 4, and 5 (N = 363). Girls were judged superior writers, but there were no gender differences in writing self-efficacy after controlling for writing aptitude. However, girls expressed that they were better writers than were other boys or girls in their class or in their school to a greater degree than did boys. Only writing self-efficacy beliefs and aptitude predicted writing performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
134
2
14

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(166 citation statements)
references
References 50 publications
16
134
2
14
Order By: Relevance
“…Pajares and Johnson (1996), for example, indicate that writing self-efficacy has a direct link to high school students" achievement as measured by their writing-essay performance. These results are also confirmed in later studies of students in other grades, (Pajares & Valient, 1997;Pajares, Miller & Johnson, 1999). It is noticeable however, that although there is a considerable body of literature on L1 writing self-efficacy, little is evident in the field of L2 writing.…”
Section: Self-efficacy and L2 Writingsupporting
confidence: 74%
“…Pajares and Johnson (1996), for example, indicate that writing self-efficacy has a direct link to high school students" achievement as measured by their writing-essay performance. These results are also confirmed in later studies of students in other grades, (Pajares & Valient, 1997;Pajares, Miller & Johnson, 1999). It is noticeable however, that although there is a considerable body of literature on L1 writing self-efficacy, little is evident in the field of L2 writing.…”
Section: Self-efficacy and L2 Writingsupporting
confidence: 74%
“…What is surprising, however, is the fact that buoyancy related positively with one's superficial and automated learning. Emotional and physiological states (e.g., a heightened state of anxiety), consistent with the work of Bandura (1997) and existing studies [56][57][58], reflect positively with one's inclination towards habitual action and automated learning. Students who express high emotional and physiological states (e.g., anxiety) would tend to exhibit more preference towards superficial learning and study habits and behaviors that reflect a sense of work-avoidant and non-serious practices.…”
Section: The Potency Of Antecedents: What Do They Dosupporting
confidence: 70%
“…A heightened state of anxiety, for example, is related to one's inefficacy beliefs for learning and self-regulation. This line of evidence, as shown in the work of Pajares and colleagues [56][57][58], is significant, theoretically, and may extend to the outcome of academic engagement and disengagement. Students who have a high state of anxiety and/or exhibit other affective responses would more likely feel disengaged from classroom learning and schooling, altogether.…”
Section: The Emphasis On Academic Engagement and Achievement Outcomementioning
confidence: 65%
“…Mathematical self-efficacy may be expressed as an important factor on mathematical performance. In their studies, Pahlavan Sadegh (3), Nasr Isfahani (4), Kabiri (5), Pajares et al (6), Pirhosseinloo (7) and Wilkins et al, (8) reported direct and indirect effect of mathematical selfefficacy on mathematical achievement. Mathematical self-efficacy could be defined as evaluation of individuals' confidence in their abilities to successful performance or completion of duty or solving a certain mathematical problem (9,10).…”
Section: Introductionmentioning
confidence: 99%